Future skills the 20 skills and competencies everyone needs to succeed in a digital world - Marr, Bernard (John Wiley & Sons, Inc., 2022)
"The 4th industrial revolution is transforming the world of work. Digitization and technologies such as AI, robotic process automation, extended reality, cloud computing, big data, blockchains, etc. are automating, augmenting and adding jobs. The skills people will need to succeed in this new world of work are very different from the skills that made people succeed in the past. There is often a misconception that all we need in the future are coding or technology skills. That couldn't be further from the truth. While we clearly need people with technical knowledge, we need individuals that have an understanding of technology, but focus on the skills humans excel at, such as creativity, critical thinking, interpersonal communication and leadership. Future Skills is about understanding what skills are required to succeed in the future workplace and how to acquire and boost those skills. The book describes the twenty most important skills for the future of work, outlines why they are so valuable, and provide tips and resources to help the reader improve those skills."--
Includes bibliographical references and index. - Online resource; title from digital title page (viewed on October 24, 2022)
Keywords: Technological literacy; Workplace literacy; Culture technologique; Alphabétisation en milieu de travail